2013
DOI: 10.1016/b978-0-12-411546-0.00006-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility and Neurotransmitters in Tourette Syndrome

Abstract: Family studies have consistently shown that Tourette syndrome (TS) is a familial disorder and twin studies have clearly indicated a genetic contribution in the etiology of TS. Whereas early segregation studies of TS suggested a single-gene autosomal dominant disorder, later studies have pointed to more complex models including additive and multifactorial inheritance and likely interaction with genetic factors. While the exact cellular and molecular base of TS is as yet elusive, neuroanatomical and neurophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 95 publications
0
36
0
1
Order By: Relevance
“…Several studies suggested for the first time that abnormalities in histaminergic signaling may contribute to rare diseases, e.g. Tourette syndrome, demonstrating a linkage between gene expression and the pathobiology of this disease [89]. The latter finding encouraged researchers to further investigate the effect of H3R polymorphism on risperidone efficacy and its potential as a genetic marker for predicting the therapeutic effect of risperidone, and suggested novel pharmacological links between H3R polymorphism and risperidone [90].…”
Section: Alzheimer's Diseasementioning
confidence: 97%
“…Several studies suggested for the first time that abnormalities in histaminergic signaling may contribute to rare diseases, e.g. Tourette syndrome, demonstrating a linkage between gene expression and the pathobiology of this disease [89]. The latter finding encouraged researchers to further investigate the effect of H3R polymorphism on risperidone efficacy and its potential as a genetic marker for predicting the therapeutic effect of risperidone, and suggested novel pharmacological links between H3R polymorphism and risperidone [90].…”
Section: Alzheimer's Diseasementioning
confidence: 97%
“…Transdiagnostic approaches may shed light on the biology underlying this symptom continuum and hold the promise to identify targets for the development of personalized treatments that are still lacking. ADHD, ASD, OCD, and TS all have a complex and highly heterogeneous genetic architecture with both common and rare genetic variants contributing to their etiology (4,(9)(10)(11)(12). Consequently, identifying and confirming genetic susceptibility factors has been challenging, demanding large samples for initial discovery and even larger samples for replication.…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state functional connectivity MRI has implicated deviation of connectivity in the fronto-parietal network, important for online adaptive control [7,8]. Although TS has classically been linked to dopamine dysfunctioning, recent studies have pointed to the involvement of other neurotransmitter systems, most notably glutamate (see [8] for a review).At least five current major limitations hamper the field of brain imaging studies in TS: (1) there has been a strong focus on TS in adults with underrepresentation of studies in children and adolescents with TS; (2) there is a lack of longitudinal MRI studies; (3) the potentially confounding Tourette syndrome (TS) is a fascinating disorder, being at the cross-roads of a neurological movement disorder and a neuropsychiatric disorder; in many cases, the movements and vocalizations are not entirely beyond a patient's voluntary control and some of its features share similarities with the symptoms of obsessive-compulsive disorder and/or the stereotyped movements associated with autism spectrum disorder. An interesting feature is the often intricate link between the type and pattern of an affected individual's tics with his or her environment.…”
mentioning
confidence: 99%
“…Functional structural and diffusion magnetic resonance imaging (MRI) have also pointed to immature and anomalous patterns of functional and structural connectivity in resting state networks such as the default mode network [5,6]. Resting-state functional connectivity MRI has implicated deviation of connectivity in the fronto-parietal network, important for online adaptive control [7,8]. Although TS has classically been linked to dopamine dysfunctioning, recent studies have pointed to the involvement of other neurotransmitter systems, most notably glutamate (see [8] for a review).…”
mentioning
confidence: 99%
See 1 more Smart Citation